Aktualisasi Panca Kesadaran Santri dalam Moderasi Islam Pendidikan Pesantren - Pathollah, Akhmad Ghasi; Hosaini, Hosaini (Edukais : Jurnal Pemikiran Keislaman, 2023)
This study aims to explore and analysis the actualization of the five consciousnesses of santri in the Islamic Moderation of pesantren alumni. The reason is that the five values internalized in pesantren education and applied in daily life while in pesantren do not necessarily become actual and consistent characters when in the community. In this context, the religiousness of santri becomes necessary to be studied as a form of actualization of the potential of the five consciousnesses of santri who are crammed while in pesantren. This research uses a descriptive qualitative method with a case study type. The data collection techniques used are observation, documentation and depth-interview. In collecting data, this research uses the Miles and Huberman interactive model, namely; data reduction, data presentation, conclusion drawing. In testing the validity of the data, researchers used triangulation, namely source triangulation, method triangulation, peer discussion and member check. The results of this study; the actualisation of the five consciousnesses of santri in the religiousness of the pesantren alumni community in the form of behaviour based on Islamic teachings, concern for knowledge, the desire to fight and contribute in the community and the tendency to involve themselves in organisations ranging from local to national scope. All of these forms of actualisation are based on a moderate way of religion with principles that are not extreme and non-violent. The contribution of the findings in this study is religious moderation in society based on the five consciousnesses of santri.